Increased Serum Levels of Soluble TNF-α Receptor Is Associated With ICU Mortality in COVID-19 Patients - Mortaz, Esmaeil; Tabarsi, Payam; Jamaati, Hamidreza; Dalil Roofchayee, Neda; Dezfuli, Neda K.; Hashemian, Seyed MohammadReza; Moniri, Afshin; Marjani, Majid; Malekmohammad, Majid; Mansouri, Davood; Varahram, Mohammad; Folkerts, Gert; et al. (Frontiers in Immunology, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) has infected over 10M patients and resulted in more than 0.5M deaths worldwide. The major clinical feature of severe COVID-19 patients requiring ventilation is acute Respiratory Distress Syndrome (ARDS) possibly associated with a cytokine storm. Objectives: To elucidate serum levels of TNF- and soluble TNF-Receptor 1 (sTNFR1) in patients with severe and mild COVID-19 disease as determinants of disease severity. Methods: We determined serum TNF-α and sTNFR1 concentrations in 46 patients with laboratory-confirmed COVID-19 (17 patients with severe disease within the intensive care unit [ICU] and 29 non-severe, non-ICU patients) and 8 healthy controls at admission using ELISA. Subjects were recruited between March-May 2020 at the Masih Daneshvari Hospital Tehran, Iran. Results: Serum levels of sTNFRI (p<0.0001) were significantly higher in ICU patients than in non-ICU patients and healthy controls. 16/17 patients in ICU died compared to no deaths in the other groups. Serum TNF-α levels were greater in ICU and non-ICU patients than in the healthy control group (p<0.0001). The sTNFRI concentration in ICU (r=0.79, p=0.0002) and non-ICU (r=0.42, p=0.2) patients positively correlated with age. The concentration of sTNFRI in ICU patients was negatively correlated with ESR. Conclusions: The study demonstrates that the concentration of sTNFRI was higher in ICU patients with severe COVID-19 disease and may be a biomarker of disease severity and mortality. Future studies should examine whether lower levels of systemic sTNFR1 at admission may indicate a better disease outcome.